Tanggung Jawab Hukum Perusahaan Multinasional dalam Rantai Pasok Global: Analisis terhadap Pelanggaran Hak Asasi Manusia dalam Aktivitas Bisnis - Cameron Santoso (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The expansion of multinational corporations in global supply chains has created complex legal challenges related to the protection of human rights within international business activities. Transnational production networks often involve suppliers located in developing countries with limited regulatory oversight, increasing the risk of labor exploitation, environmental damage, and social conflicts affecting local communities. This research analyzes the legal responsibility of multinational corporations for human rights violations occurring within global supply chains by examining relevant national and international legal frameworks. The study employs normative legal research using statutory and conceptual approaches to evaluate regulations governing corporate accountability. Legal instruments such as Law Number 39 of 1999 on Human Rights, Law Number 40 of 2007 on Limited Liability Companies, and Law Number 25 of 2007 on Investment establish the legal basis for corporate obligations toward society and the environment. International frameworks, particularly the United Nations Guiding Principles on Business and Human Rights, reinforce expectations for corporate human rights due diligence across global operations.